2015
DOI: 10.1249/mss.0000000000000497
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Thigh-Worn ActiGraph and activPAL Monitors to Classify Posture and Motion

Abstract: Differences in data processing algorithms may have resulted in the observed disagreement in posture and activity classification between thigh-worn ActiGraph and activPAL. Despite between-monitor agreement in classifying sitting time under free-living conditions, ActiGraph appears to be more sensitive to free-living upright walking motions than activPAL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
77
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(89 citation statements)
references
References 30 publications
9
77
0
Order By: Relevance
“…A recent study in adults reported excellent accuracy for both the activPAL and ActiGraph GT3X+ (attached to the thigh) when classifying sitting, standing and stepping (the majority of the activities were correctly classified more than 90% of the time for both monitors) during a laboratory-based protocol (Steeves et al, 2015). In addition, the ActiGraph (attached to the thigh) provided similar estimates of sitting time compared to the activPAL (64% versus 62%) under free-living conditions (Steeves et al, 2015). Carr and Mahar (2012) reported that the hip-based ActiGraph correctly classified 90% of time spent sedentary (sedentary was defined as sitting and standing still) when using ≤ 150 counts per minute.…”
Section: Methodological Decisions When Measuring Sedentary Behavior Amentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in adults reported excellent accuracy for both the activPAL and ActiGraph GT3X+ (attached to the thigh) when classifying sitting, standing and stepping (the majority of the activities were correctly classified more than 90% of the time for both monitors) during a laboratory-based protocol (Steeves et al, 2015). In addition, the ActiGraph (attached to the thigh) provided similar estimates of sitting time compared to the activPAL (64% versus 62%) under free-living conditions (Steeves et al, 2015). Carr and Mahar (2012) reported that the hip-based ActiGraph correctly classified 90% of time spent sedentary (sedentary was defined as sitting and standing still) when using ≤ 150 counts per minute.…”
Section: Methodological Decisions When Measuring Sedentary Behavior Amentioning
confidence: 99%
“…However, the recent ActiGraph models (GT3X and up) also provide the possibility of classifying posture through the use of equations that estimate inclination from raw triaxial data. A recent study in adults reported excellent accuracy for both the activPAL and ActiGraph GT3X+ (attached to the thigh) when classifying sitting, standing and stepping (the majority of the activities were correctly classified more than 90% of the time for both monitors) during a laboratory-based protocol (Steeves et al, 2015). In addition, the ActiGraph (attached to the thigh) provided similar estimates of sitting time compared to the activPAL (64% versus 62%) under free-living conditions (Steeves et al, 2015).…”
Section: Methodological Decisions When Measuring Sedentary Behavior Amentioning
confidence: 99%
“…Acceleration data can be used to identify the intensity of a given movement as well as its underlying pattern (i.e., frequency, duration) over predetermined epochs [41,42]. This device has demonstrated acceptable validity and reliability in children [43,44]. …”
Section: Methodsmentioning
confidence: 99%
“…threshold, for example, has been reported as only 50% accurate in detecting sedentary time in laboratory studies. 12 Triaxial accelerometers have the potential to act as inclinometers to help identify body posture, dependent on wear location. Accelerometers worn on the thigh (Figure 1) provide greater ability to robustly distinguish between standing (thigh vertical) and sitting/lying (thigh horizontal) in comparison with the waist or the wrist.…”
Section: Measuring Sb Using Accelerometersmentioning
confidence: 99%